Iteration:Again: 13 Public Art Projects across Tasmania - Marcon, Marco (punctum books, 2013)
Iteration:Again documents and reflects upon a series of thirteen temporary public art commissions by twenty-one Australian and international artists that took place across Tasmania from September 18 to October 15, 2011. Produced by Contemporary Art Spaces Tasmania and David Cross, in conjunction with seven partner curators, Iteration:Again presents a compelling array of temporary artworks in largely unexpected places throughout Tasmania. Working to transform our experience of place for a moment in time, each commission seeks to address how temporary interventions or responses by artists to public sites, environments and buildings can serve to open up new ways of understanding Tasmania as a place with very complex cultural, social and spatial resonances. How it might be possible to introduce transformative elements that challenge the notion of a fixed or definitive artwork grounded in one location? By asking the artists to make four different chapters or 'iterations' over the course of a four-week period, David Cross challenged each practitioner to think through how change or processes of transition may function to make the art experience an unstable and contingent one. This idea of incorporating change into the work highlights a growing interest by artists in emphasizing art as a potentially theatrical or even fictive medium with the audience experiencing different moments or stages of encounter over a number of weeks. The idea provided for the possibility of narrative sequences, formal investigations, or temporal shifts that saw key additions or subtractions over time. Each commission sought to recast our understanding of public artwork from a discrete event or viewing experience, to a suite of experiences.